Polypharmacy and predictors of high level polypharmacy in patients with diabetic nephropathy in a tertiary care hospital - Jose, Josephine V.; Devi, Padmini; Satish, Renuka (International Journal of Basic & Clinical Pharmacology, 2019)
Background: Diabetic Nephropathy (DN) is the leading cause of end-stage renal disease. Polypharmacy is common in DN as pharmacotherapy is complex with multimorbidity. The objectives of the study are to assess the prevalence and patterns of polypharmacy and to determine the predictors of high-level polypharmacy among patients with diabetic nephropathy in a tertiary care hospital. Methods: A prospective observational study was conducted among adult patients with DN visiting nephrology outpatient department (March 2015 to August 2016). Data on demography, disease characteristics, and treatments were collected. Baseline data were summarized using descriptive statistics. Categorical variables and predictors of polypharmacy were analysed using Chi-square tests and multivariate logistic regression respectively. Results: Mean age of patients was 58.14±10.44 years with male preponderance (72.7%). A majority of patients had comorbidities (76%). Hypertension was the most common co-morbidity (98.7%). Majority (64%) were in DN stage 4-5 and 58% of patients were undergoing hemodialysis. Mean number of drugs prescribed was 9.25±2.5. Anti-hypertensives (95.3%) were the major drug class prescribed. Polypharmacy (>5 drugs) was noticed in 95.3% patients and high-level polypharmacy (>10 drugs) in 46.7%. Presence of ≥3 comorbidities is a significant predictor of high-level polypharmacy (OR-1.414: 95% CI (1.008, 1.982), p=0.045). Conclusions: Polypharmacy was noticed in a majority of patients with high level polypharmacy in more than one third of patients with DN. Presence of ≥3 comorbidities were found to be significant predictor of high-level polypharmacy.